Model to predict inhomogeneous protein–sugar distribution in powders prepared by spray drying. (November 2016) - Grasmeijer, Niels; Frijlink, Henderik W.; Hinrichs, Wouter L.J.
Abstract: A protein can be stabilized by spray drying an aqueous solution of the protein and a sugar, thereby incorporating the protein into a glassy sugar matrix. For optimal stability, the protein should be homogeneously distributed inside the sugar matrix. The aim of this study was to develop a model that can predict the distribution of protein and sugar in an evaporating droplet using bovine serum albumin (BSA) and trehalose as model protein and sugar, respectively. This was achieved by expanding a previously developed model that was able to predict the growth or shrinkage of inhaled droplets in the airways (Grasmeijer, Frijlink & Hinrichs, 2016). The droplet was considered to consist of a finite number of concentric spherical shells in which the change in concentration of components was calculated in time, enabling the prediction of concentration gradients inside the droplet. It was found that during evaporation of the droplet, an inhomogeneous protein–sugar distribution was formed even when surface active properties were not considered. The relatively large protein molecule was predicted to accumulate much faster at the surface of the droplet than the sugar due to slower diffusion, resulting in a lower sugar/protein ratio at the surface of the particle than in the center. For a mixture of BSA and trehalose, not considering surface active properties, it was predicted that 60% of protein was incorporated in the powder at a lower sugar/protein ratio than when protein and sugar would have been homogeneously distributed, which may hamper efficient protein stabilization. These predictions can be used to more accurately adapt the initial composition of the solution to ensure proper stabilization of the protein, for example by simply increasing the amount of sugar to increase the sugar/protein ratio at the surface. Or, if this is limited by the desired loading, changing the drying conditions to slow down the drying rate. Highlights: A freely available model was developed for droplet drying. Protein and sugar distribution throughout a drying droplet was simulated. Protein accumulated at the droplet surface even without surface active properties. About 60% w/w of BSA was located in regions with below average sugar/protein ratio. The model can be adapted and expanded.